The Density of Perineuronal Nets Increases With Age in the Inferior Colliculus in the Fischer Brown Norway Rat - Mafi, Amir M.; Hofer, Lindsay N.; Russ, Matthew G.; Young, Jesse W.; Mellott, Jeffrey G. (Frontiers in Aging Neuroscience, 2020)
Age-related hearing loss, one of the most frequently diagnosed disabilities in industrialized countries, may result from declining levels of GABA in the aging inferior colliculus (IC). However, the mechanisms of aging and subsequent disruptions of temporal processing in elderly hearing abilities are still being investigated. Perineuronal nets (PNs) are a specialized form of the extracellular matrix and have been linked to GABAergic neurotransmission and to the regulation of structural and synaptic plasticity. We sought to determine whether the density of PNs in the IC changes with age. We combined Wisteria floribunda agglutinin (WFA) staining with immunohistochemistry to glutamic acid decarboxylase in three age groups of Fischer Brown Norway (FBN) rats. The density of PNs on GABAergic and non-GABAergic cells in the three major subdivisions of the IC was quantified. Results first demonstrate that the density of PNs in the FBN IC increase with age. The greatest increases of PN density from young to old age occurred in the central IC (67% increase) and dorsal IC (117% increase). Second, in the young IC, PNs surround non-GABAergic and GABAergic cells with the majority of PNs surrounding the former. The increase of PNs with age in the IC occurred on both non-GABAergic and GABAergic populations. The average density of PN-surrounded non-GABAergic cells increased from 84.9 PNs/mm2 in the young to 134.2 PNs/mm2 in the old. While the density of PN-surrounded GABAergic cells increased from 26 PNs/mm2 in the young to 40.6 PNs/mm2 in the old. The causality is unclear, but increases in PN density in old age may play a role in altered auditory processing in the elderly, or may lead to further changes in IC plasticity.